PHENYLKETONURIA IN CHILDREN: DIAGNOSTICS, CLINIC, TREATMENT - T.V. Bushuyeva ("Paediatrician" Publishers LLC, 2010)
At the present times there is a quickened interest in hereditary metabolic diseases that can be revealed by neonatal screening. The list of these diseases includes a phenylketonuria. The interest is conditioned by the opportunity of timely efficient correction of metabolic disorders, first of all by the diet. The article describes the questions of epidemiology, diagnostics, treatment dietotherapy and other methods of treatment of phenylketonuria in children. Key words: phenylketonuria, neonatal screening, dietotherapy, specialized food.(Voprosy sovremennoi pediatrii - Current Pediatrics. 2010;9(1):157-160)